Association between hysterectomy for benign indications and the risk of breast cancer: a systematic review and meta- analysis - Liu, Wenjing; Lu, Tingting; Yang, Jingqi; Liu, Jie (Frontiers in Oncology, 2025)
ObjectivesTo determine the association between hysterectomy performed for benign indications and the risk of developing BC.MethodsA literature search was conducted in PubMed, Embase, and the Cochrane Library from database inception up to December 11, 2024. Eligible studies were observational design. Relative ratios (RRs) and 95% confidence intervals (CIs) were pooled using a random-effects model, I2 was used to assess the heterogeneity between studies.ResultsThis meta-analysis included 12 studies, consisting of 4 case-control studies and 8 cohort studies. The pooled analysis of case-control studies indicated that hysterectomy reduced the risk of BC (RR = 0.839, 95% CI: 0.707-0.995, P = 0.043, I2 = 81.661%). However, the pooled analysis of cohort studies did not observe a significant association between hysterectomy and the occurrence of BC (RR = 0.981, 95% CI: 0.927-1.037, P = 0.495, I2 = 60.319%).ConclusionsThe present study reveals a protective effect of hysterectomy on the occurrence of BC in case-control studies. However, more studies, especially cohort studies, are needed to elucidate the potential beneficial effects of hysterectomy on the development of BC.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024596235, identifier CRD42024612164.